Parent Education tentang Pendidikan Seks bagi Remaja: Studi Pengembangan Model Konseling Keluarga Berbasis Sekolah - Nani Nuranisah Djamal; Cece Rakhmat; Syamsu Yusuf; Nandang Rusmana (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2020)
This study aims to examine the effectiveness of the parent education program in increasing parental knowledge about sex education for adolescents, exercising the ability of parents in planning sex education and obtaining an assessment of parent education activities followed by parents. Research using the R & D (Research and Development) method with concurrent embedded strategy design. The participants were 20 parents who have early adolescents in one of Bandung's public high schools. The parental knowledge measurement tool was designed based on the concept of knowledge according to the Revised Bloom Taxonomy, while the effectiveness of the parent education program was adapted from Instruments for Training and Learning Evaluation from Leslie Rae. The results of the study prove that parent education activities are effective in increasing parental knowledge about sex education for adolescents, especially conceptual and procedural knowledge. Research recommendations are directed towards further improvement and development of the model, as an alternative to the development of multi-disciplinary cooperation in dealing with student problems.